2020
DOI: 10.5194/acp-20-12609-2020
|View full text |Cite
|
Sign up to set email alerts
|

Climatological impact of the Brewer–Dobson circulation on the N<sub>2</sub>O budget in WACCM, a chemical reanalysis and a CTM driven by four dynamical reanalyses

Abstract: Abstract. The Brewer–Dobson circulation (BDC) is a stratospheric circulation characterized by upwelling of tropospheric air in the tropics, poleward flow in the stratosphere, and downwelling at mid and high latitudes, with important implications for chemical tracer distributions, stratospheric heat and momentum budgets, and mass exchange with the troposphere. As the photochemical losses of nitrous oxide (N2O) are well known, model differences in its rate of change are due to transport processes that can be sep… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 110 publications
2
13
0
Order By: Relevance
“…Calculations on JRA-55 reanalysis were performed on 6-hourly snapshots and calculations on free-running WACCM output were done on monthly-mean data. As our calculations from WACCM were performed on coarser temporal resolution data, we validated them by reproducing results of the TEM tracer budget from Minganti et al (2020) and found consistent results (not shown).…”
Section: Transformed Eulerian Mean Tracer Budgetsupporting
confidence: 59%
See 1 more Smart Citation
“…Calculations on JRA-55 reanalysis were performed on 6-hourly snapshots and calculations on free-running WACCM output were done on monthly-mean data. As our calculations from WACCM were performed on coarser temporal resolution data, we validated them by reproducing results of the TEM tracer budget from Minganti et al (2020) and found consistent results (not shown).…”
Section: Transformed Eulerian Mean Tracer Budgetsupporting
confidence: 59%
“…Therefore, attempts to account for imprints of dynamical influences on near-surface concentration signals should include stratosphere-troposphere advection modulated by the QBO and its seasonally changing phase relationship. This work augments existing studies that use a TEM tracer budget to quantify stratosphere-troposphere exchange (Abalos et al, 2020;Minganti et al, 2020). It advances the existing body of literature about synchronizations between the annual cycle of ozone concentrations and the QBO (Gray & Dunkerton, 1990) by examining phase unlocking patterns in the lower stratospheric advection of tracers.…”
Section: Discussionmentioning
confidence: 72%
“…Recent studies have stated a substantial uncertainty in the climatological strength and trends of the stratospheric BDC and age of air in current-generation reanalyses (e.g. Abalos et al, 2015;Miyazaki et al, 2016;Chabrillat et al, 2018;Ploeger et al, 2019). Among the reanalyses considered, JRA-55 was shown to have the fastest BDC and MERRA-2 was shown to have the slowest BDC, with ERA-Interim-based results in between.…”
Section: Discussionmentioning
confidence: 99%
“…Diallo et al, 2012;Monge-Sanz et al, 2012). However, more recent efforts combining different newest-generation reanalysis data sets have shown a large dependency of BDC trend estimates on the reanalysis used, for both residual circulation (Abalos et al, 2015;Miyazaki et al, 2016) and age of air diagnostics (Chabrillat et al, 2018;Ploeger et al, 2019). In particular, no consensus has been reached amongst reanalyses, including ERA-Interim reanalysis from the ECMWF (Dee et al, 2011), JRA-55 from the Japanese Meteorological Agency (Kobayashi et al, 2015), and MERRA-2 from the National Aeronautics and Space Administration (Gelaro et al, 2017) concerning decadal age of air and BDC changes.…”
Section: Introductionmentioning
confidence: 99%
“…While usually used in the context of stratospheric chemical data assimilation (e.g. Errera et al (2019) ), the Chemistry Transport Model (CTM) of the system has been also used to study of the evolution of the stratospheric composition (Chabrillat et al, 2018;Prignon et al, 2019;Minganti et al, 2020). Here, BASCOE was run for the period 25 Sept-1 Oct 2008 where wind and temperature were taken from the ERA-Interim reanalysis (Dee et al, 2011).…”
Section: Bascoementioning
confidence: 99%